SOLVENT EXTRACTION OF IRON IONS FROM HYDROCHLORIC ACID SOLUTIONS - Farouq, Rania; Selim, Yehia (Journal of the Chilean Chemical Society, 2017)
In this study Methyl Isobutyl Ketone (MIBK) and acetophenone (Methyl Phenyl Ketone) are presented as suitable agents for removal of Fe(III) from concentrated hydrochloric acid solutions. An extensive study applying 4 parameters was carried out: Time (5, 10,15,20,30 and 60 minutes), Stirring rate (200, 300, 400 and 500 r.p.m), Solvent to HCl Ratio (5%, 10%, 14% and 16%), and initial concentration of Fe ions in crude HCl (95.24, 126 ppm, 330 ppm and 1955 ppm).The best Condition was found to be 30 min – 400 r.p.m – 14 %. The distilled water was used to strip Fe ions out of MIBK; In order to get most of the MIBK dissolved in both the concentrated HCl and water. Diluents were used such as benzene, kerosene and xylene. Xylene gives better recovery of about 96%.